Acid gas treatment agent and acid gas treatment method
Mg-Al-based LDHs with tailored pore size and sulfate ion content improve adsorption of nitrogen oxides and sulfur oxides, extending breakthrough time and reducing regeneration frequency, thus enhancing the efficiency of acidic gas treatment.
Patent Information
- Application Number
- JP2024096345
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-07-25
- Filing Date
- 2024-06-14
- Publication Date
- 2025-02-06
- Estimated Expiration
- 2044-06-14
AI Technical Summary
Conventional Mg-Al LDHs used for treating acidic exhaust gases have low adsorption ability for nitrogen oxides and sulfur oxides, quickly reach saturation, and require frequent regeneration, leading to high labor and cost burdens.
Mg-Al-based LDHs with specific average pore diameter (30 nm or more), sulfate ion content (1 mass% or less), and controlled particle size distribution (D50 of 13.0 to 16.0 μm, D90/D10 of 55 to 75) are used to enhance adsorption ability and prolong breakthrough time.
The modified Mg-Al-based LDHs exhibit improved adsorption capacity and extended breakthrough time, reducing the frequency of regeneration and enhancing removal efficiency of acidic substances.
Smart Images

Figure 2025018945000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an acidic gas treatment agent and an acidic gas treatment method for removing acidic substances such as hydrogen chloride, sulfur oxides, and nitrogen oxides from combustion exhaust gas. [Background technology]
[0002] The exhaust gas from combustion in thermal power plants and waste incineration contains hydrogen chloride, sulfur oxides (SO x ) and nitrogen oxides (NO x For this reason, various methods are being used to treat acid gases that contain such acidic substances in order to remove the acidic substances.
[0003] Regarding a treatment method for removing such acidic substances, the present applicant has proposed a treatment method and treatment agent for acidic exhaust gas that utilizes an Mg-Al-based layered double hydroxide (hereinafter, layered double hydroxide may be abbreviated as LDH (Layered Double Hydroxide)) as an efficient treatment technology capable of simultaneously treating multiple types of acidic substances (see Patent Document 1, and Non-Patent Documents 1 and 2). For example, Non-Patent Document 1 describes that carbonate-type Mg-Al-based LDH can efficiently remove hydrogen chloride gas, and that carbonate-type Mg-Al-based LDH slurry can remove not only hydrogen chloride gas but also sulfur oxide gas. Non-Patent Document 2 describes that the removal rate of hydrogen chloride gas increases by increasing the amount of carbonate-type Mg-Al-based LDH.
[0004] Furthermore, the applicant of the present application has proposed a system for regenerating and repeatedly using used treating agents for Mg-Al-based LDH (see Patent Documents 2 and 3). Patent Document 2 proposes an on-site regeneration method in which treated exhaust gas is used for regeneration, and Patent Document 3 proposes a method for treating acidic exhaust gas and regenerating used treating agents using hydroxide-type Mg-Al-based LDHs. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 6954569 [Patent Document 2] Patent No. 6898627 [Patent Document 3] Patent No. 7130197 [Non-patent literature]
[0006] [Non-Patent Document 1] Journal of the Society of Inorganic Materials, 2014, Vol.21, p.197-203 [Non-Patent Document 2] Atmospheric Pollution Research, 2020, Vol.11, Issue 2, p.290-295 Summary of the Invention [Problem to be solved by the invention]
[0007] Conventional Mg-Al-based LDHs used to treat acidic exhaust gases do not necessarily have a high adsorption capacity for acidic substances such as nitrogen oxides and sulfur oxides, and they quickly reach saturation, necessitating frequent regeneration treatment, which results in a large burden of labor and cost for the regeneration treatment process. For this reason, there is a demand for Mg-Al-based LDHs with a long breakthrough time in order to increase the adsorption capacity of the acidic substances in the acidic exhaust gas and reduce the frequency of regeneration treatment.
[0008] The present invention has been made to solve such problems, and has an object to provide an acidic gas treatment agent and an acidic gas treatment method using an Mg-Al-based LDH that has high adsorption capacity for acidic substances and a long breakthrough time, in order to reduce the frequency of regeneration treatment of the treatment agent. [Means for solving the problem]
[0009] The present invention is based on the discovery that, when the average pore size and sulfate ion content of the Mg-Al-based LDH are within a predetermined range, an acid gas treatment agent having high adsorption capacity for acidic substances and a long breakthrough time can be obtained.
[0010] The present invention provides the following means. [1] An acid gas treatment agent comprising an Mg-Al-based layered double hydroxide having an average pore diameter of 30 nm or more as measured by nitrogen gas adsorption and a sulfate ion content of 1 mass% or less. [2] The agent for treating acidic gas according to [1], wherein the Mg-Al-based layered double hydroxide is a carbonate type or a hydroxide type. [3] The agent for treating acidic gas according to [1] or [2], wherein the elemental molar ratio of Mg to Al in the Mg-Al-based layered double hydroxide is 2 to 3. [4] The agent for treating acidic gas according to any one of [1] to [3], wherein the Mg-Al-based layered double hydroxide has a cumulative 50% volume particle diameter D50 of 13.0 to 16.0 μm and a ratio of the cumulative 90% volume particle diameter D90 to the cumulative 10% volume particle diameter D10 (D90 / D10) of 55 to 75. [5] A molded body comprising any one of the acid gas treatment agents described in [1] to [4]. [6] A method for treating an acidic gas, comprising contacting the agent for treating an acidic gas according to any one of [1] to [4] or the molded article according to [5] with an acidic gas containing an acidic substance, thereby removing the acidic substance. Effect of the Invention
[0011] According to the present invention, an agent for treating acidic gas and a method for treating acidic gas using Mg-Al-based LDHs having high adsorption capacity for acidic substances and long breakthrough time are provided. Furthermore, according to the present invention, the frequency of regeneration treatment of the agent for treating acidic gas can be reduced, and the efficiency of removing acidic substances in acidic gas can be improved. [Brief description of the drawings]
[0012] [Figure 1] 1 is a graph showing a breakthrough curve in an acid gas adsorption test of an example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] In this specification, a numerical range expressed using "~" means that the numerical values before and after "~" are the lower and upper limits. A preferred numerical range can be any combination of the preferred lower and upper limits.
[0014] The agent for treating acidic gas of the present invention comprises an Mg-Al-based LDH having an average pore diameter of 30 nm or more as measured by a nitrogen gas adsorption method and a sulfate ion content of 1 mass % or less.
[0015] The Mg-Al LDHs are a hydroxide base layer ([Mg 2+ 1-x Al 3+ x (OH) 2 ]) and interlayer anion (A n- ) and the intermediate layer ([(A n- ) x / n ·yH 2 These nanoparticles have a structure in which the hydroxide base layer has a positive charge equivalent to x, and negatively charged anions that compensate for this exist between the layers, making this a non-stoichiometric compound. Although Mg-Al-based LDHs are naturally occurring clay minerals, they are generally synthesized by known methods.
[0016] When an acidic gas is contacted with the Mg-Al-based LDH, the acidic substances such as hydrogen chloride, sulfur oxides, and nitrogen oxides can be captured between the layers while maintaining the hydroxide base layer. The interlayer anions are ion-exchanged with anions derived from the acidic substances, thereby exerting the adsorption ability for the acidic substances. The adsorption ability for the acidic substances decreases with the decrease in the interlayer anions due to the progress of ion exchange, and the acidic gas treatment agent of the Mg-Al-based LDH breaks through. The Mg-Al-based LDH of the acid gas treatment agent thus broken through can be regenerated and reused by anion exchange with interlayer anions by a known method.
[0017] From the viewpoints of good adsorption ability for acidic substances and ease of repeated use through regeneration, the Mg-Al-based LDH is preferably a carbonate- or hydroxide-type Mg-Al-based LDH in which the interlayer anion is a carbonate ion or a hydroxide ion.
[0018] In addition, from the viewpoint of the ion (anion) exchange capacity of the interlayer anions and the solid solubility limit of the aluminum ion, which is a trivalent metal ion, the Mg-Al-based LDH has an elemental molar ratio of Mg to Al (Mg / Al molar ratio) of preferably 2 to 3, more preferably 2 to 2.8, and even more preferably 2 to 2.5.
[0019] The agent for treating acidic gas of the present invention has a high adsorption capacity for acidic substances and a long breakthrough time because the Mg-Al-based LDH has an average pore size and a sulfate ion content within a given range.
[0020] Specifically, the average pore diameter is 30 nm or more, preferably 31 nm or more, and more preferably 32 nm or more, as measured by a nitrogen gas adsorption method. The average pore diameter by nitrogen gas adsorption method is calculated as 4V / A from the specific surface area A obtained by the BET one-point method from the adsorption isotherm and the one-point total pore volume V for Mg-Al-based LDH. Specifically, it is calculated by measurement using a specific surface area / pore distribution measurement device.
[0021] There is a correlation between the average pore size of the Mg-Al-based LDH and its adsorption capacity for acidic substances. When the average pore size is 30 nm or more, it becomes easier for acidic substances to enter the adsorption sites between the layers of the Mg-Al-based LDH, thereby increasing the adsorption capacity for acidic substances. From a practical standpoint, the upper limit of the average pore size is preferably 50 nm or less, more preferably 48 nm or less, and further preferably 45 nm or less.
[0022] The method for controlling the average pore size of the Mg-Al LDH is not particularly limited. The average pore size can be enlarged to 30 nm or more by, for example, a mechanochemical method, and specifically, a method of contacting with water, drying, and grinding and mixing by a mechanochemical method can be mentioned. The Mg-Al LDH can enlarge the average pore size by applying mechanical stress, since some of the pores are deformed and enlarged. Examples of the pulverization method include a method using a cone crusher, a roll crusher, a cutter mill, an autogenous grinder, a stamp mill, a stone mill, etc. When the amount of Mg-Al-based LDH to be pulverized is small, a home coffee mill can also be used.
[0023] The sulfate ion content of the Mg-Al-based LDH in the agent for treating an acidic gas of the present invention is 1 mass % or less, preferably 0.9 mass % or less, and more preferably 0.8 mass % or less. The sulfate ion content is calculated from the elemental analysis value of the sulfur element by X-ray fluorescence analysis. The sulfate ions in the Mg-Al-based LDH may be contained, for example, as those derived from the raw materials for producing the Mg-Al-based LDH.
[0024] There is a correlation between the sulfate ion content of Mg-Al LDH and its adsorption capacity for acidic substances, and sulfate ions present between the layers of Mg-Al LDH inhibit the adsorption of acidic substances. By keeping the sulfate ion content at 1 mass% or less, anion exchange between the interlayer anions and anions derived from acidic substances is facilitated, resulting in a significant improvement in the adsorption capacity for acidic substances and a longer breakthrough time for the acid gas treatment agent.
[0025] The method for controlling the sulfate ion content of the Mg-Al-based LDH is not particularly limited. For example, a method for reducing the sulfate ion content to 1 mass% or less includes a method of contacting the Mg-Al-based LDH with an aqueous sodium carbonate solution to replace the sulfate ions contained in the Mg-Al-based LDH with carbonate ions. Contact with an aqueous sodium carbonate solution is preferable because it can expand the pore size of the Mg-Al-based LDH by the action of hydration swelling, etc.
[0026] When Mg-Al-based LDH is brought into contact with an aqueous sodium carbonate solution, it is preferable to control the average pore size by pulverizing and mixing using a mechanochemical method or the like after the contact and drying. Since Mg-Al-based LDH tends to become lumpy in a wet state, it is more reasonable to pulverize only once after sufficiently drying the LDH as a process for controlling the average pore size and sulfate ion content.
[0027] From the viewpoint of the flow efficiency of the acidic gas, the Mg-Al-based LDH in the acidic gas treatment agent of the present invention preferably has a cumulative 50% volume particle diameter D50 of 13.0 to 16.0 μm and a ratio of the cumulative 90% volume particle diameter D90 to the cumulative 10% volume particle diameter D10 (D90 / D10) of 55 to 75. It is more preferable that the Mg-Al-based LDH has a D50 of 13.5 to 15.5 μm and a D90 / D10 of 60 to 70. D50, D10 and D90 are determined from a volume-based particle size distribution measured by a laser diffraction / scattering particle size analyzer. Specifically, they can be measured by the method described in the Examples.
[0028] The form of the agent for treating acidic gas of the present invention is not particularly limited as long as the average pore size and sulfate ion content of the Mg-Al-based LDH are within the ranges specified in the present invention. The acidic gas treatment agent of the present invention may be processed appropriately from the viewpoint of its usage mode, ease of handling, etc., and may be in the form of granules granulated by a known method such as extrusion granulation. It may also be used as a molded product molded into pellets, spherical particles, etc. using a binder, etc. In other words, the molded product of the present invention contains the acidic gas treatment agent.
[0029] From the viewpoint of ease of handling, the particle size of the molded product is preferably 1 to 5 mm, more preferably 2 to 4 mm, and further preferably 2.5 to 3.5 mm. Here, the particle size of the molded product corresponds to the diameter if the molded product is spherical, and in the case of a pellet, it means the length of the part where the gap between the plates is the largest when the pellet is sandwiched between two parallel plates (the maximum gap between the two plates). A molded product with a particle size of 1 to 5 mm is a granular material that does not pass through a sieve with 1 mm openings but passes through a sieve with 5 mm openings when sieved.
[0030] The method for treating an acidic gas of the present invention involves contacting the above-mentioned agent or molded article for treating an acidic gas of the present invention with an acidic gas containing an acidic substance, thereby removing the acidic substance. The acidic substance is not particularly limited, but as described above, for example, when it is hydrogen chloride, sulfur oxides, nitrogen oxides, etc., these acidic substances can be suitably adsorbed and removed by the acid gas treatment agent or molded article of the present invention.
[0031] As described above, the acidic gas treatment agent of the present invention exhibits the excellent effects of the present invention by virtue of the Mg-Al-based LDH having an average pore size and a sulfate ion content within a predetermined range. However, the agent can also be used in combination with, for example, an LDH composed of another metal element having an adsorption ability for acidic substances. EXAMPLES
[0032] The present invention will be described in detail below with reference to examples. The present invention is not limited to the following examples, and various modifications are possible without departing from the gist of the present invention.
[0033] [Sample analysis] For the samples of the following Examples and Comparative Examples, the average pore size and sulfate ion content were measured as follows. (Average pore diameter) The average pore diameter was measured by the nitrogen gas adsorption method using a specific surface area / pore distribution measuring device ("BELSORP (registered trademark)-mini", manufactured by Microtrack-Bel Co., Ltd.). (Sulfate ion content) Elemental analysis was performed using an X-ray fluorescence analyzer, and the sulfur element content was converted into the sulfate ion content.
[0034] (Cumulative volume 50% particle size D50, cumulative volume 90% particle size D90, and cumulative volume 10% particle size D10) Using a laser diffraction / scattering particle size distribution analyzer (MT-3300 EXII, manufactured by Microtrack Bell Co., Ltd.), the sample powder was added to a sample circulator in which a 0.025% by mass aqueous solution of sodium hexametaphosphate was circulated (transmittance 80-95%), and the volumetric particle size distribution was measured to determine D50 and D90 / D10.
[0035] [Sample preparation] Example 1 8.6 g of sodium carbonate was dissolved in 1 L of ion-exchanged water and heated to 70 ° C. to prepare an aqueous sodium carbonate solution. 100 g of Mg-Al-based LDH (1) (manufactured by Sakai Chemical Industry Co., Ltd.; Mg / Al molar ratio 2) was added to this aqueous sodium carbonate solution and stirred at 70 ° C. for 1 hour to mix. The resulting mixture was filtered, and the solid matter on the filter paper was washed with ion-exchanged water until the conductivity of the washing liquid was 100 μS / cm or less. The washed solid matter was dried at 105 ° C. and then ground in a household coffee mill for 30 seconds to obtain Mg-Al-based LDH (2) as a sample (average pore size: 32.0 nm, sulfate ion content: 0.55 mass%, D50: 14.5 μm, D90 / D10: 65.8).
[0036] Comparative Example 1 The Mg-Al-based LDH (1) used in Example 1 was used as a sample without being treated (average pore size: 28.5 nm, sulfate ion content: 2.76 mass %, D50: 30.2 μm, D90 / D10: 81.0).
[0037] Comparative Example 2 The Mg-Al-based LDH (1) used in Example 1 was ground for 30 seconds in a household coffee mill to obtain a Mg-Al-based LDH (3) as a sample (average pore size: 29.5 nm, sulfate ion content: 2.75 mass%, D50: 12.0 μm, D90 / D10: 48.7).
[0038] [Acid gas adsorption test] 0.15 g of sample was placed in a reaction tube (inner diameter 17 mm) packed with glass wool, and the glass wool was placed on top to prepare a reaction tube with the sample placed therein so as to have air permeability. This reaction tube was heated in a tubular electric furnace set at a temperature of 150° C. Hydrogen chloride gas was passed through the reaction tube in a downward flow (linear velocity 1.0 m / min) while controlling the supply amount with a mass flow controller so as to obtain a concentration of 300 ppm by mass (balance gas: nitrogen). The concentration of hydrogen chloride gas at the outlet of the reaction tube was measured by an infrared spectrometer for gas analysis.
[0039] In Fig. 1, the horizontal axis is the flow time of hydrogen chloride gas, and the vertical axis is the concentration ratio of hydrogen chloride gas at the inlet and outlet of the reaction tube (outlet concentration C out / inlet concentration C in ) is shown in the breakthrough curve of the sample. 1, the samples of Comparative Examples 1 and 2 had a breakthrough time of less than 60 minutes, whereas the sample of Example 1 had a long breakthrough time of 110 minutes or more. In addition, the sample of Example 1 had a smaller concentration ratio of hydrogen chloride gas at the outlet of the reaction tube than the samples of Comparative Examples 1 and 2, confirming that the sample had a high adsorption capacity for hydrogen chloride gas.
Claims
1. An agent for treating acidic gas, comprising an Mg-Al-based layered double hydroxide having an average pore diameter of 30 nm or more as measured by a nitrogen gas adsorption method and a sulfate ion content of 1 mass % or less.
2. 2. The agent for treating acidic gas according to claim 1, wherein the Mg-Al based layered double hydroxide is a carbonate type or a hydroxide type.
3. 2. The agent for treating acidic gas according to claim 1, wherein the Mg-Al based layered double hydroxide has an elemental molar ratio of Mg and Al of 2 to 3.
4. 2. The agent for treating acidic gas according to claim 1, wherein the Mg—Al-based layered double hydroxide has a cumulative 50% volume particle diameter D50 of 13.0 to 16.0 μm and a ratio of a cumulative 90% volume particle diameter D90 to a cumulative 10% volume particle diameter D10 (D90 / D10) of 55 to 75.
5. A molded article comprising the acid gas treatment agent according to claim 1.
6. A method for treating an acidic gas, comprising contacting the agent for treating an acidic gas according to claim 1 or the molded article according to claim 5 with an acidic gas containing an acidic substance, thereby removing the acidic substance.
Citation Information
Patent Citations
Method for regenerating carbonate-type layered double hydroxide and acidic exhaust gas treatment equipment
JP6898627B2
Acidic exhaust gas treatment method, acidic exhaust gas treatment equipment, and incineration facility
JP6954569B1
Acidic exhaust gas treatment method, acidic exhaust gas treatment equipment, and incineration facility
JP7130197B1